2020
DOI: 10.1016/j.immuni.2019.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Restrain Interleukin-2- and Blimp-1-Dependent Acquisition of Cytotoxic Function by CD4+ T Cells

Abstract: Summary In addition to helper and regulatory potential, CD4 + T cells also acquire cytotoxic activity marked by granzyme B (GzmB) expression and the ability to promote rejection of established tumors. Here, we examined the molecular and cellular mechanisms underpinning the differentiation of cytotoxic CD4 + T cells following immunotherapy. CD4 + transfer into lymphodepleted animals or regulatory T (Treg) cell depletion promoted Gzm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 66 publications
(86 reference statements)
10
124
0
Order By: Relevance
“…B cells, and ~75% of DLBCL tumors, constitutively express MHC-II, and nearly all cell lineages can express class II after exposure to IFNg and other cytokines. CD4+ T cells can participate in tumor clearance by directly lysing tumor cells as well as by enhancing tumor lysis by other immune cell types (Alspach et al, 2019;Sledzinska et al, 2020), and MHC-II may represent an important target for non-conventional CD8+ T cells that can be induced by specific viral vectors (Hansen et al, 2013). As MHC-II may be critically important for DLBCL patient survival (Ennishi et al, 2019), the dual role of some genes we identified is likely clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…B cells, and ~75% of DLBCL tumors, constitutively express MHC-II, and nearly all cell lineages can express class II after exposure to IFNg and other cytokines. CD4+ T cells can participate in tumor clearance by directly lysing tumor cells as well as by enhancing tumor lysis by other immune cell types (Alspach et al, 2019;Sledzinska et al, 2020), and MHC-II may represent an important target for non-conventional CD8+ T cells that can be induced by specific viral vectors (Hansen et al, 2013). As MHC-II may be critically important for DLBCL patient survival (Ennishi et al, 2019), the dual role of some genes we identified is likely clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional analysis revealed a polyfunctional helper and cytotoxic phenotype characterized by the expression of T-bet and Blimp-1. While T-bet ablation restricted the production of IFN-γ, loss of Blimp-1 prevented GzmB expression in response to IL-2, suggesting that two independent programmes required for the polyfunctionality of tumour-reactive cytotoxic CD4 + T cells [ 144 ]. In addition, blocking IFN α and β receptor 1 (IFNAR1) on Tregs significantly decreases both the Tregs immunosuppressive function and myeloma progression.…”
Section: Tumour Immunotherapy Strategies Targeting Tregsmentioning
confidence: 99%
“…However, some mature CD4 T cells, cytotoxic CD4 T cells (CD4-CTLs or Th-CTLs), may act similarly as cytotoxic CD8 T cells in killing their target cells through the secretion of granzyme B and perforin but in an MHCII-restricted manner [13][14][15]. The transcriptional factor Eomes (a T-box transcription factor critical for the development of functional natural killer (NK) and CD8 T cells), T-bet, and Blimp1 are critical for inducing the expression of cytotoxicity-associated genes in CD4-CTLs [16][17][18]. Similar to CD8 T cells, CD4-CTLs display increased Runx3 but reduced ThPOK expression [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%